The Relationship Between Food Insecurity and the Nutritional Status and Mental Health of University Students - Grace Carol Sipasulta; Kalasta Ayunda Putri (CV. Get Press Indonesia, 2025)
This study aims to examine the relationship between food insecurity, nutritional status, and mental health among university students. A cross-sectional study was conducted at a state university in West Sumatra, Indonesia. Data were collected using descriptive statistics, Chi-Square tests, and logistic regression analysis. The independent variable in this study was food insecure, which was measured using the Food Insecurity Experience Scale (FIES) instrument. A total of 372 students from different faculties at the university participated in the study. Logistic regression analysis was used to determine the predictors of both conditions. The results of this study show that students with food security were nearly twice as likely to be undernourished compared to their food-secure peers (OR = 1.89; 95% CI: 1.10-3.24; p = 0.021), and those with more severe food security faced an even higher risk (OR=2.14, 95% confidence interval (CI): 1.20-3.83). Students with food-security had more than double the odds of experiencing mild to severe depression (P=0.005), while those with severe food-insecurity had an even greater risk (P0.001), highlighting the substantial impact of inadequate food access on student well-being. These findings are expected to serve as a basis for universities in formulating intervention policies, ranging from the provision of healthy food to psychological support services, as well as enriching the national literature on this issue.